Women, Economics and Finance in Ancient Rome: Old Challenges and Current Issues - Valério Gaia, Deivid (Revista Archai, 2023)
The image of the Roman woman, which has survived to this day and imposed itself almost as the only possibility for the ancient scholarship, is the domiseda: the housewife, mother, and spinner. In addition to the investigations of this traditional depiction, which steered the research on Roman women, the issues of our time and the advances in scientific research constantly bring us new perspectives, approaches, and problems around this object of study. This inevitably motivates us to question the role of women in the business and finance world in Ancient Rome. Is it possible to write an economic and financial history of Roman women? What are the limits of this endeavor? This article addresses the insertion of women in the business and finance world, as well as some of the multiple possibilities of writing the History of Women from the Economic and Social History viewpoint. The time frame is restricted to the end of the Republic and the imperial period. This article is therefore divided into three parts: first, an introduction to the discussion of the situation of women in the domus; secondly, methodological assumptions to the study of women and their placement in economic and financial life; and, finally, some examples ofwomen from three different social groups who appear involved in credit relations in the documentation.